Gambaran Tingkat Pengetahuan Keselamatan dan Kesehatan Kerja Pada Petugas Pengambil Sampah Kota Samarinda: Overview of the Level of Occupational Safety and Health Knowledge of Waste Collectors in Samarinda City - Bramiasto, Muhammad Raka; Duma, Krispinus; Danial (Jurnal Medika : Karya Ilmiah Kesehatan, 2024)
Occupational Safety and Health (OSHE) is a form of improving and maintaining the rights of all workers physically, mentally and socially, supervising people, work tools, materials and the work environment so that every worker is free from physical, mental, emotional or painful disturbances in conditions physiological and psychological workers, in order to prevent work-related accidents. Garbage collector are vulnerable jobs with various risks of work accidents, because they are directly exposed to community waste disposal. The purpose of this study was to describe the level of OSHE knowledge of garbage collectors in Samarinda City. The research design is descriptive observational with 80 research respondents. Using a simple random sampling technique using a questionnaire. This is a one-variable descriptive observational study. The results of this study show that the OSHE knowledge level of Garbage Collectors is (94%) in the "Good" category, OSHE knowledge is based on the education level of High school (42%) in the "Good" category, Junior High School (23%) in the "Less" category, Elementary School (34%) "Less" category. Based on length of service, it is classified into 1-5 years with results (57%) in the "Good" category, 6-10 years (31%) in the "Less" category and workers more than 10 years (12%) in the "Less" category. The conclusion of this study is that the OSHE level of knowledge of garbage collection officers in Samarinda City is "Good" with the characteristics of the education level respondents who have the "Good" category from the High school class and in terms of length of work characteristics who have the "Good" category from the 1-5 year worker group.